REPRESENTATION OF POLITICAL AND SOCIAL PROCESSES OF THE COLONIAL PERIOD IN UZBEK HISTORIOGRAPHY (1920–2020) - Erkinboyev Fozilbek Zokirjon oʻgʻli (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article explores how the political and social dynamics of the colonial period in Central Asia, particularly during the Russian Empire and early Soviet rule, have been represented in Uzbek historiography from 1920 to 2020. The paper identifies key trends and transformations in historical narratives, analyzing the ideological influences that shaped historiographical discourse during the Soviet era, the independence period, and modern academic scholarship. Drawing upon primary texts, historical monographs, and educational materials, the study traces the shifting interpretations of colonialism, resistance movements, reforms, and identity formation in Uzbekistan.